2014
DOI: 10.2460/ajvr.75.9.818
|View full text |Cite
|
Sign up to set email alerts
|

In vivo proton magnetic resonance spectroscopy for the evaluation of hepatic encephalopathy in dogs

Abstract: (1)H MRS aided in the diagnosis of hepatic encephalopathy in dogs, and findings supported the assumption that ammonia is a neurotoxin that manifests via glutamine-glutamate complex derangements. Use of (1)H MRS may provide clinically relevant information in patients with subclinical hepatic encephalopathy, equivocal results of bile acids tests, and equivocal ammonia concentrations or may be helpful in monitoring efficacy of medical management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…In tick‐borne encephalitis infection, neurons are the primary target cells of flavivirus infection after entering the central nervous system; thus, the depletion of N‐acetyl aspartate concentration observed in positive tick‐borne encephalitis patients in this study may be due to neuronal dysfunction due to neuro‐inflammation or neuronal loss due to neuronal death. N‐acetyl aspartate has been reported to be lower than normal in dogs with neoplasias, noninfectious meningoencephalitis, and hepatic encephalopathy . In cases of noninfectious meningoencephalitis in dogs and people with viral infectious diseases and multiple sclerosis, a recovery of N‐acetyl aspartate after improvement with treatment has been demonstrated .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In tick‐borne encephalitis infection, neurons are the primary target cells of flavivirus infection after entering the central nervous system; thus, the depletion of N‐acetyl aspartate concentration observed in positive tick‐borne encephalitis patients in this study may be due to neuronal dysfunction due to neuro‐inflammation or neuronal loss due to neuronal death. N‐acetyl aspartate has been reported to be lower than normal in dogs with neoplasias, noninfectious meningoencephalitis, and hepatic encephalopathy . In cases of noninfectious meningoencephalitis in dogs and people with viral infectious diseases and multiple sclerosis, a recovery of N‐acetyl aspartate after improvement with treatment has been demonstrated .…”
Section: Discussionmentioning
confidence: 99%
“…The use of 1 H MRS is increasing in veterinary medicine. Several studies have been recently published, reporting the metabolite concentration in the brain of healthy dogs, as well as in brain pathology such as hepatic encephalopathy, intracranial neoplasias and meningoencephalitis . The brain bioprofile in dogs, as well as in humans or other species, affected with tick‐borne encephalitis by using 1 H MRS has not been reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies exist in the veterinary literature that describe pilot research or limited clinical applications of magnetic resonance spectroscopy . The available veterinary literature supports the feasibility of magnetic resonance spectroscopy as an imaging technique for the canine brain . Metabolite concentrations in the brains of both healthy and diseased tissues in dogs using both single‐ and multi‐voxel spectroscopy are described .…”
Section: Discussionmentioning
confidence: 99%
“…In people, magnetic resonance spectroscopy is clinically valuable for characterizing various brain lesions, including neoplastic, infectious, and inflammatory lesions, as well as traumatic brain injury . In contrast, information regarding magnetic resonance spectroscopy in the veterinary literature is limited . Two methods of performing magnetic resonance spectroscopy exist: single‐voxel spectroscopy and multi‐voxel spectroscopy .…”
Section: Introductionmentioning
confidence: 99%
“…In veterinary medicine, clinical MRI can only be performed under general anesthesia. Recently, relative metabolite concentrations and their ratios in the brain of healthy beagle dogs under general anesthesia have been published [ 15 17 ], as well as a few clinical studies [ 26 , 27 ] using different anesthetic protocols. Since the influence of anesthetics on the canine brain bioprofile at 3 Tesla is actually not known, the purpose of the study reported here was to determine the possible effects of the commonly used anesthetics isoflurane, sevoflurane, propofol and alfaxalone on canine brain bioprofile assessed with single voxel short echo time proton magnetic resonance spectroscopy at a field strength of 3.0 Tesla.…”
Section: Introductionmentioning
confidence: 99%